Minimum and Complete Fluidization Velocity for Sand-Palm Shell Mixtures, Part II: Characteristic Velocity Profiles, Critical Loading and Binary Correlations - Chok, Vui; Gorin, Alexander; Chua, Han (Science Publications, 2010)
Problem statement: In Part I of this research, the main features of the fluidization behaviorand characteristic velocities had been reported. Approach: In the present research, the mixturescharacteristic velocity profiles for various sand sizes, palm shell sizes and weight percents werepresented. It was recognized that there are instances where the characteristic values remain nearlyunchanged from its pure sand values. This regime of constant values can be observed in bothcompartments and can be established depending on the bed properties. The term ?Critical loading? isthen selected to define the maximum palm shell content (size and weight percent) that can be presentin the mixtures where the characteristic velocities remain absolutely of pure sand values. Results: Thecritical loading increases with the increase of sand size but decreases with the increase of palm shellsize. Moreover, it can be observed that the critical loading generally decreases with the increase inparticle size ratio, although exception is sighted in the combustor for the mixture with the largest sandsize. Overall, the largest sand size has the highest critical loading. Meanwhile, the selected correlationsare able to describe the qualitative variation in the characteristic velocities. However, quantitatively,these correlations are unsatisfactory as they are either over-estimate or under-estimate.Conclusion/Recommendations: It is desirable to establish the regime of critical loading since the mixture characteristic velocities can be pre-determined using bed material properties made up frompure sand (inert) values. Within this regime, a single operational velocity can be set for respectivecompartment that is independent from variation of palm shell size and weight percent in the mixtures(especially during combustion or gasification). Ultimately, the state of fluidization (e.g., bubbling orvigorously fluidized) and mixing/segregation condition that depend on relative magnitude ofoperational and characteristic velocities can be identified and maintained.